Assessing current and future areas of ecological suitability for Lutzomyia shannoni in North America - DeWinter, Sydney; Nichol, Grace K.; Fernandez-Prada, Christopher; Greer, Amy L.; Weese, J. Scott; Clow, Katie M. (Parasites & vectors, 2025)
Background In the Americas, sand flies of the Lutzomyia genus are the vectors of pathogens of human and animal health significance. Lutzomyia shannoni is suspected to transmit vesicular stomatitis virus, along with Leishmania mexicana and Leishmania infantum (causative agents of leishmaniases). Despite the suspected vector potential of Lu. shannoni , significant knowledge gaps remain, including how ongoing climate changes could facilitate their range expansion. The objectives of this study were to predict the current and future ecological suitability of regions across North America for Lu. shannoni and to identify variables driving ecological suitability. Methods Occurrence records were obtained from the Global Biodiversity Information Facility, Disease Vectors Database, the National Museum of Natural History (Smithsonian Institution) and published literature on Lu. shannoni surveillance and capture. Historical climate data from 1991–2020, along with projection data for Shared Socioeconomic Pathways 2–4.5 and 3–7.0 were obtained. An additional terrestrial ecoregions layer was applied. The ecological niche model was created using maximum entropy (MaxEnt) algorithms to identify regions which currently are or may become ecologically suitable for Lu. shannoni . Results Currently, regions in eastern, western and southern Mexico, along with the Midwest, southeastern and eastern regions of the USA are ecologically suitable for Lu. shannoni . In the future, ecological suitability for Lu. shannoni is expected to increase slightly in the northeastern regions of the USA and in Atlantic Canada, and to decrease in the southeastern reaches of Mexico. Degree-days below 0 °C (spring and autumn), precipitation as snow (summer and winter), terrestrial ecoregions, number of frost-free days (summer), Hargreaves climatic moisture deficit (summer), degree-days above 5 °C (autumn) and Hogg’s climatic moisture index (summer) were all identified as predictors of ecological suitability. Conclusions The findings from this study identified climate and environmental variables driving the ecological suitability of regions for Lu. shannoni and can be used to inform public health professionals of high-risk regions for exposure at present and into the future. Graphical abstract